Review of elementary mathematics - Rich, Barnett (Schaum's outline series, 1977)
Fundamentals of arithmetic: number - Fundamentals of arithmetic: addition and multiplication - Subtraction and division - Fractions - Decimals - Per cents - Fundamentals of algebra: laws and operations - Fundamentals of algebra: equations and formulas - Fundamentals of geometry: lines and angles - Geometric figures and formulas - Ratios, proportins and rates - Squares and square roots, law of pythagoras, similar triangles, trigonometry - Signed numbers.